Anti-TNF-α and hydralazine drug-induced lupus - Maria Victória Quaresma; Fred Bernardes Filho; Fernanda Brandão de Oliveira; Mercedes Prates Pockstaller; Maria Fernanda Reis Gavazzoni Dias; David Rubem Azulay (Sociedade Brasileira de Dermatologia, 2015)
AbstractDrug-induced lupus is a rare drug reaction featuring the same symptoms as idiopathic lupus erythematosus. Recently, with the introduction of new medicines in clinical practice, an increase in the number of illness-triggering implicated drugs has been reported, with special emphasis on anti-TNF-α drugs. In the up-to-date list, almost one hundred medications have been associated with the occurrence of drug-induced lupus. The authors present two case reports of the illness induced respectively by hydralazine and infliximab, addressing the clinical and laboratorial characteristics, diagnosis, and treatment.